Pengaruh Regulasi, Inklusi Keuangan, dan Teknologi Keuangan terhadap Perilaku Keuangan, Risiko Keuangan, dan Ketahanan Keuangan dengan Menggunakan Tata Kelola Keuangan yang Baik sebagai Moderator pada Usaha Mikro, Kecil, dan Menengah (UMKM) di Kecamatan Gedeg, Kabupaten Mojokerto - Amelia Kusniawati; Tri Ratnawati; Ida Ayu Sri Brahmayanti (CV SCRIPTA INTELEKTUAL MANDIRI, 2025)
MSMEs in Gedeg District are facing a decline in the number of MSMEs and financial vulnerability, which requires analysis of external factors, namely Regulation, Financial Inclusion, and Financial Technology, as well as internal factors, namely Financial Behavior and Financial Risk, which shape Financial Resilience. This study aims to examine the influence of these three external factors on MSMEs' financial behavior, risk, and resilience, and analyze the mediating role of financial behavior and risk, as well as the moderation of Good Financial Governance (GFG). Using a quantitative approach with primary data obtained from 310 MSMEs through a purposive sampling survey and analyzed using PLS-SEM. The results show that regulation, inclusion, and fintech have a significant effect on financial behavior and risk, which then mediate their influence on financial resilience. However, the direct effect of Regulation and Financial Inclusion on resilience is statistically insignificant. Good Financial Governance (GFG) as a moderator shows insignificant results, implying that governance practices alone may not strengthen resilience without risk management mechanisms and financial behavior. These findings underscore the importance of synergy between financial access, effective regulation, financial literacy, and transparent governance in enhancing the resilience of MSMEs.